(untitled) - Gerschlager, Caroline (New York, N.Y., 2005)
This volume focuses on modern economic analyses of deception in markets. Modern economic theory encompasses a variety of approaches and the contributors offer a systematic account of how different approaches to modern economics deal with dishonesty and cheating in the marketplace. Analyses are presented from the perspective of the economics of information, game theory, behavioral economics and finance, new institutional economics and the history of economic thought.
Keywords: Information theory in economics,Fraud,Business ethics,Institutional economics,Economics